Irrigation and Fertigation Scheduling for Peach and Citrus Crops - Hasan, M; Sirohi, N.P.S (Journal of Agricultural Engineering, 2006)
A completely automatic drip irrigation system used in fertigation for peach and citrus was designed and installed at the IARI farm. A separate fertigation control unit was made for operation and control of fertigation of fruit crops in the orchard. Fertigation scheduling comprised two important components i.e. estimation of crop water and nutrient requirement and their application in correct dosage at appropriate stage. The water requirement varied in different months and at various stages ofthe crop. Hydraulic fertilizer pumps were used for the fertigation through solenoid operated hydraulic valves. The most suitable dose of nitrogen, phosphorus and potassium was found to be 30, 15 & 30 ppm in peach and 60, 30 & 60 ppm in citrus during the initial stages of growth and fruiting. The annual consumption of major nutrients per tree was found to be 354 gm for nitrogen, 160gm for phosphorus and 345 gm for potassium. Water soluble fertilizers viz., Potassium nitrate, Ammonium nitrate and Phosphoric acid were used for fertigation. Potassium nitrate was the only source ofpotassium while nitrogen was found in both potassium and ammonium nitrate. Phosphoric acid served the twin purpose of phosphorous source as well as cleaning of lateral pipes of drip irrigation, whenever so required.